The Transmedia and Post-Literary Emergence in Adaptation - Lea, David (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
In the context of the global market, the main role of platforms in current society provokes the unstoppable growing of a digital infrastructure characterized by users’ interactions in the net. This participatory model has also directly involved the collaborative character within different art works in the adaptation processes, leaving behind a tradition of dichotomic struggle between original-novel and copy-film. Consequently, Hutcheon and Bortolotti rescue the Dawkins’ term of “replication” to explain the distinct media expressions which are produced repeating preexistent arguments in their narrative forms and how resulting transformations actualize or evolve (hi)stories. The transmedia phenomena define great franchises, streaming or VoD aesthetics, where audience emerges as direct mediator of the plot, from the purely post-literary medium, bringing together authorship and reception (see twitterature) to the fusion with cinema in its adaptations. The final goal is to illustrate the emergency of digital paradigm and the specific weight of media and performative turn.